Babken Arakelyan - Zardaryan, Mkrtich H. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
It is not easy to gather and organise your thoughts in order to write about an individual that had a significant impact on your professional and (partially) personal life. Babken Arakelyan was exactly that person for me, the author of these lines. Much has been written about the life and accomplishments of Academician, Professor Arakelyan. In fact, he was worthy of all that. This scholar, a student of the noteworthy Armenologist, Orientalist, Director of the Hermitage, Hovsep Orbeli, composed many valuable works regarding the history and culture of Classical and Medieval Armenia. For decades, he was in charge of the excavations of Garni, Armavir, Artashat, and other sites. He was also the founder of the Institute of Archaeology and Ethnography NAS RA, taught for many years, and was the supervisor of dozens of dissertations. Armenia’s school of Classical archaeology was formed through his efforts. However, there is no need to list all the accomplishments of this meritorious scholar’s fruitful life in detail here, since that is accessible on the NAS RA official website. I would more likely stress out all of Babken Arakelyan’s personal qualities that characterised him especially as a TEACHER.